Reaping the Whirlwind : The Taliban Movement in Afghanistan - Griffin, Michael (GHQ, Rawalpindi Army Education Publishing House, 2003)
"Reaping the Whirlwind provides the first comprehensive profile of the Taliban in the twenty-first century. Drawing on numerous interviews with key protagonists, conducted over a period of several years, Michael Griffin provides a fascinating eyewitness account of the Afghan conflict. He explains the origins and beliefs of the Taliban movement, its religious and political ethos, and the character of its particular brand of so-called Islamic fundamentalism. Crucially, he examines the controversial nature of the Taliban's international links with the U.S., Saudi Arabia, and other vested interests. Griffin also explores the Taliban's connections with Osama bin Laden, drug barons and drug dealers, and the CIA's ambiguous relationship with what is often viewed as an international Islamist conspiracy." "Situated between Asia, the Middle East and the former Soviet states, Afghanistan has historically fulfilled the role of an artifical 'buffer state'. Resource rich and strategically important, it has been of particular interest since the end of the Cold War to Saudi Arabia, Russia, Pakistan and the United States, as well as to drug barons, arms dealers and oil corporations. Afghanistan's unstable and problematic history has been further complicated in recent years by the emergence of the Taliban - perhaps the most conservative and least understood Islamic movement in the world."
Include Map, Abbreviations, Chronology, Note and Index.
Afghanistan's unstable history has been further complicated by the emergence of the Taliban - one of the most conservative and least understood Islamic movements. This book provides an account of the background to the ongoing conflict in the area, and a profile of the Taliban movement itself.
Keywords: Afghanistan -- Islamic Fundamentalism -- Islam and Politics -- Islam and State -- Taliban